2016
DOI: 10.1007/s10863-016-9660-1
|View full text |Cite
|
Sign up to set email alerts
|

Arginine kinase shows nucleoside diphosphate kinase-like activity toward deoxythymidine diphosphate

Abstract: Arginine kinase (AK) (ATP: L-arginine phosphotransferase, E.C. 2.7.3.3) catalyzes the reversible transfer of ATP γ-phosphate group to L-arginine to synthetize phospho-arginine as a high-energy storage. Previous studies suggest additional roles for AK in cellular processes. Since AK is found only in invertebrates and it is homologous to creatine kinase from vertebrates, the objective of this work was to demonstrate nucleoside diphosphate kinase-like activity for shrimp AK. For this, AK from marine shrimp Litope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…This protein is found only in invertebrates, in the vertebrates, its counterpart is creatinine kinase. Arginine kinase is involved in ATP transformations and phosphoarginine synthesis [18]. Studies conducted in Italy have shown that it is a minor allergen that sensitizes 10-15% of the population of patients allergic to shrimp allergens, which is consistent with our findings [12].…”
Section: Discussionsupporting
confidence: 92%
“…This protein is found only in invertebrates, in the vertebrates, its counterpart is creatinine kinase. Arginine kinase is involved in ATP transformations and phosphoarginine synthesis [18]. Studies conducted in Italy have shown that it is a minor allergen that sensitizes 10-15% of the population of patients allergic to shrimp allergens, which is consistent with our findings [12].…”
Section: Discussionsupporting
confidence: 92%
“…The kinetic parameters determined for the substrate L-arginine were K m 1.7 mM and V max 27.8 μmol min −1 mg protein −1 ; within the range described for other arthropods. The horseshoe crab Limulus polyphemus ( Blethen, 1972 ), the scorpion Palamneus phipsoni ( Arjunwadkar & Raghupathi Rami Reddy, 1985 ) and tarantula Dugesiella hentzi ( Blethen & Kaplan, 1968 ) had a K m between 0.08 and 0.67 mM; in insects Cissites cephalotes ( Tanaka et al, 2007 ), Locusta migratoria ( Ilg & Werr, 2012 ; Wu et al, 2007 ), Periplaneta americana ( Brown & Grossman, 2004 ), K m was between 0.49–1.0 mM; and in the crustacean Litopenaeus vannamei ( Lopez-Zavala et al, 2016 ), Euphausia superba ( Si et al, 2014 ), the K m was 0.3 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…S-methyl-L-cysteine, a sulfur-containing amino acid present in garlic, has been reported to exhibit antilipidemic activity ( 50 52 ). dGDP, also known as deoxythymidine diphosphate, serves as an intermediate molecule during the process of DNA synthesis ( 53 ). Adenosine, a purine nucleoside involved in both DNA and RNA synthesis, plays a crucial role in cellular growth and development.…”
Section: Discussionmentioning
confidence: 99%